The business cycle implications of banks' maturity transformation - Martin M. Andreasen; Marcelo Ferman; Pawel Zabczyk (European Central Bank (ECB), 2012)
This paper develops a DSGE model where banks use short-term deposits to provide firms with long-term credit. The demand for long-term credit arises because firms borrow in order to finance their capital stock which they only adjust at infrequent intervals. Within an RBC framework, we show that maturity transformation in the banking sector dampens the consumption and investment response to a technology shock. Our model also implies that the average deposit rate is less persistent than the average long-term loan rate, which we show is in line with corporate interest rate data in the US.
Keywords: E32; E44; E22; G21; 330; banks; DSGE model; Financial Frictions; long-term credit; maturity transformation